Unemployment Among University Graduates In Pengkalan Chepa, Kelantan - Nurul Aishah, Muhamad (Universiti Malaysia Sarawak, UNIMAS, 2021)
Unemployment is one of the problems in the economy that is caused by a labour imbalance which indicates that the amount of labour that offered more than the amount of manpower requested. The height of the unemployment rate occur will reflect good or bad the economy of a country or a region. In addition, one of the most important issues for a country or area is this unemployment problem will have an impact on a variety of crime, social politics, and poverty. In Kelantan, the unemployment rate is relatively moderate compared to other states in Malaysia. This can be seen from the development of the graduate unemployment rate in Kelantan in 2020 of 6.0%. Unemployment that occurs theoretically, of course, there are several indicators that affect it, among which are population growth and education. A study on unemployment among graduates needs to combine all the different opinions from different sources and analyse those opinions to obtain accurate results. A study on the factors, effects and recommendations involved in this problem can reduce the unemployment rate in Kelantan especially in Pengkalan Chepa.